PEMANFAATAN LAHAN TELANTAR DALAM TINJAUAN UNDANG-UNDANG POKOK AGRARIA DAN EKONOMI ISLAM - Badranaya, Djaka (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2011)
Abandon efforts to land, both state owned and private, in the view of Islamic economics is not justified. Even the country with itsauthorities have the right to redistribute those asets for the prosperity of the people. It takes political will of government, consistency, and the rules of the land, which is accountable and comprehensive in order to encourage the utilization of unused land. Abandoned land use policy really is not just for big private interests in oil palm plantations, but the utilization policy is intended for the benefit and public welfare widelyDOI: